UMKM, Strategy for Ending Poverty in Sustainable Economic Development - Aloysius Dewanto Handoko; Ningrum Natasya Sirait; Mahmul Siregar; Mirza Nasution (Publikasi Indonesia, 2025)
The Indonesian government has not been optimal in promoting the development of UMKM as a strategy to achieve the SDGs. As a result, the global commitment for people around the world to enjoy a peaceful and prosperous life by 2030 is still difficult to achieve. The main issue in this paper questions the extent of the Indonesian government's efforts in promoting the development of UMKM. Using the normative juridical research method, the research findings show that UMKM play an important role in national economic development, thus they should be the focus of strategies to achieve the SDGs. Indonesia itself has policies and regulations that mandate the development of UMKM. Unfortunately, the implementation of those policies and regulations has not met expectations due to paradigmatic constraints within them. Therefore, it is recommended that the Indonesian government undertake legal reforms in the field of investment to optimize the implementation of existing policies and regulations, particularly in the field of investment, in developing UMKM.